Leading spiritually diverse organizations: a graduate course to prepare leaders - Phipps, Kelly A. (Journal of management, spirituality & religion, 2023)
Prior authors have described a variety of ways to incorporate spirituality into graduate management education. This article reports on a graduate course approaching the topic from a different vantage point: helping students build their capacity to work respectfully with religious and spiritual diversity in the workplace (Hicks, 2002). First, students were challenged to examine the nature of religious diversity in the workplace, including workplaces which purport to incorporate spirituality. Next, after reviewing the legal requirements as a minimum standard, students were challenged to formulate an informed stance on the role of spirituality in the workplace. Finally, students were asked to reflect on the beliefs that inform their leadership, including their source and effect. By helping students articulate their own beliefs respectfully and formulate an informed approach to spiritual diversity, the course modeled the desired outcome: leaders who can honor and respect the beliefs of others while simultaneously embracing their own.